Pengaruh Model Pembelajaran Numbered Head Together terhadap Kemampuan Diskusi Peserta Didik Mata Pelajaran Sejarah Kebudayaan Islam - Zuhriyyah Hidayati; Jevi Candra Dinata; Muhammad Subhan (IBTIDA, 2022)
The purpose of this study is to find out how the implementation of the NHT model affects the discussion ability of class VI students Miftahul Ulum Duriwetan in 2020/2021 in Sejarah Kebudayaan Islam subject. Numbered Head Together or numbering of thinking together is a type of cooperative learning that is fun and can motivate students to actively discuss when applied in the classroom. While the discussion is a group activity carried out by students in the classroom, to solve the problems faced by the group. The method used in this study is quasi-experiment, while the research approach used is a quantitative descriptive approach. This study used a sample of class VI MI Miftahul Ulum Duriwetan-Maduran-Lamongan students who numbered 15 students. The instruments in the study used discussion and questionnaire skills tests given to students to test the effect of implementing the NHT model. The results of this study show that with the application of the NHT model can affect the discussion ability of class VI MI Miftahul Ulum Duriwetan students. This can be proven by the average value before doing the treatment 63, while after the treatment 89. The results of the analysis use t-tests of samples pairedboosts rate and posts, namely the price of the value t-calculate = 18,565 > t-table = 2,145, while the results of the t-calculated questionnaire analysis = 9,095 > t-table = 2,145. The analysis was strengthened using IBM SPSS Statistics. Thus the researchers concluded that the application of the NHT learning model affected the discussion ability of class VI MI Miftahul Ulum Duriwetan-Maduran-Lamongan students.